2005
DOI: 10.1007/s10722-004-6084-2
|View full text |Cite
|
Sign up to set email alerts
|

Rice Diversity Collection, Conservation and Management in Northeastern India

Abstract: Rice is the principal crop of northeastern region of India, where a considerable range of diversity exists. The germplasm collection has also unfold the occurrence of large number of rice landraces in the region. Between 1985 and 2002, a total 2639 accessions of rice germplasms including their wild relatives have been collected. Most of these germplasm material have been conserved in the National Gene Bank, New Delhi following their necessary characterization and evaluation. With the establishment of the Regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 3 publications
1
55
0
1
Order By: Relevance
“…It is a home for aromatic rice diversity (Bisne and Sarawgi, 2008) and grown in almost all the states, covering more than 30 per cent of the total cultivated area (Adhikari et al, 2012;Sarma et al, 2016). From the agro horticultural view point North east is the richest reservoir for genetic variability in aromatic rice crops (Hore 2005). Because of the special flavour and economic value, aromatic rice bears special significance in the present globalized era.…”
Section: Introductionmentioning
confidence: 99%
“…It is a home for aromatic rice diversity (Bisne and Sarawgi, 2008) and grown in almost all the states, covering more than 30 per cent of the total cultivated area (Adhikari et al, 2012;Sarma et al, 2016). From the agro horticultural view point North east is the richest reservoir for genetic variability in aromatic rice crops (Hore 2005). Because of the special flavour and economic value, aromatic rice bears special significance in the present globalized era.…”
Section: Introductionmentioning
confidence: 99%
“…Their human trial showed increased level of ferritin in the blood of the anemic subjects (Annual Report, IRRI) which is an indication of improving helping eradicating anemia for the rice eating population in the world. (Hore, 2005). However the processing and nutritional qualities of such genotypes are still not studied.…”
Section: Introductionmentioning
confidence: 99%
“…稻品种多样性极为丰富, 如中国的云南和贵州 (Gao, 2003;Cui et al, 2016)、印度东北部 (Hore, 2005)、泰 国的北部 (Akimoto et al, 1999)、尼泊尔 (Bajracharya et al, 2010)、尼日尔 (Sow et al, 2014) Fig. 1 The relationship between landrace decrease rate and ration of migrant workers …”
Section: 来的大量研究表明 边远欠发达少数民族地区的水unclassified